2022
DOI: 10.1097/nna.0000000000001137
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mindfulness on Stress and Burnout of New Graduate Nurses as a Component of a Nurse Residency Program

Abstract: This evidence-based practice project assessed the impact of integrating mindfulness training into an existing nurse residency program. BACKGROUND: Stress and burnout are endemic in healthcare. The transition to practice is associated with stress and anxiety for newly graduated nurses. Evidence supports mindfulness-based interventions to mitigate stress and burnout and improve the workplace environment and patient outcomes. METHODS: This project employed a pre/post design to measure burnout, stress, and mindful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…The full results of the quality assessment are available in online supplementary table 1. All articles in this review were published between 2015 and 2022 with most studies (n=22) based in the USA 1 4 7 17 26 37–53. Two studies were based in Australia,54 55 two in the Netherlands56 57 and one each from Ireland,58 Italy,59 Portugal,60 Brazil,61 Hong Kong,12 Japan62 and Iran 63.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The full results of the quality assessment are available in online supplementary table 1. All articles in this review were published between 2015 and 2022 with most studies (n=22) based in the USA 1 4 7 17 26 37–53. Two studies were based in Australia,54 55 two in the Netherlands56 57 and one each from Ireland,58 Italy,59 Portugal,60 Brazil,61 Hong Kong,12 Japan62 and Iran 63.…”
Section: Resultsmentioning
confidence: 99%
“…Two studies were based in Australia,54 55 two in the Netherlands56 57 and one each from Ireland,58 Italy,59 Portugal,60 Brazil,61 Hong Kong,12 Japan62 and Iran 63. Twenty-seven1 4 7 12 26 37–52 54 58–61 63 studies had participants that were predominantly female, two56 57 reported more male than female participants and four17 46 53 55 did not specify gender. A total of 1617 37 39 42 44 46–48 50–54 60 61 63 articles reported that nurses were the sole participants in their studies, 526 38 43 56 57 reported physicians only, 159 reported sampling both physicians and nurses, 51 12 40 49 55 sampled a variety of healthcare workers (including allied health) and 64 7 41 45 58 62 articles used generic terminology such as healthcare professionals, hospital staff or clinical/non-clinical roles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application provides immediate access to tips and practices to equip nurses with tools to navigate stress. • Mindfulness training has been shown to increase the use of mindfulness techniques and reduce burnout and stress (McNulty et al, 2022). • In 2021, 176,762 minutes were logged in SHC's mindfulness platform.…”
Section: • Rethinkcarementioning
confidence: 99%
“…Mindfulness training has been shown to increase the use of mindfulness techniques and reduce burnout and stress(McNulty et al, 2022).• In 2021, 176,762 minutes were logged in SHC's mindfulness platform.• Stress First Aid• A set of supportive, evidence-based actions designed to promote self-care was introduced in leadership development sessions in 2021. • The Stress First Aid model includes seven elements (also known as the seven Cs): check, coordinate, cover, calm, connect, competence, and confidence.…”
mentioning
confidence: 99%